2020
DOI: 10.11604/pamj.2020.36.133.19913
|View full text |Cite
|
Sign up to set email alerts
|

Some epidemiological and clinical characteristics of metabolic syndrome in Marrakesh, Morocco

Abstract: Introduction the purpose of this study was to bring out some epidemiological and clinical characteristics of metabolic syndrome. Methods a total of 300 subjects willingly participated in the present study which was conducted at Ibn Zohr regional hospital in Marrakesh. We were interested in socio-demographic variables, body mass index (BMI) which assesses the degree of obesity of each subject. The blood parameters were determined by an adequate biochemistry automaton. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Living in the countryside was associated with a lower prevalence of MetS than living in a city, which was similar to the findings of Xi et al [16], while living in northern China was associated with a higher prevalence of MetS than living in southern China, which was also observed by Gu et al [4]. The BMI is an important measure of obesity and overall health and is closely related to MetS [17,18]. This study found that every 1 unit increase in BMI was associated with a 40.2% increase in the prevalence of MetS.…”
Section: Discussionsupporting
confidence: 83%
“…Living in the countryside was associated with a lower prevalence of MetS than living in a city, which was similar to the findings of Xi et al [16], while living in northern China was associated with a higher prevalence of MetS than living in southern China, which was also observed by Gu et al [4]. The BMI is an important measure of obesity and overall health and is closely related to MetS [17,18]. This study found that every 1 unit increase in BMI was associated with a 40.2% increase in the prevalence of MetS.…”
Section: Discussionsupporting
confidence: 83%
“…Our study showed a significantly higher prevalence of hypertension, hyperlipidemia, abdominal obesity, and MetS in males than in females. However, some other studies have found that the prevalence of MetS was higher in females than in males [ 44 , 45 ]. The different results from different studies may be explained by the differences in hormones, lipid metabolism, population diversity, cultural behaviors, lifestyle habits, and the use of different diagnostic criteria.…”
Section: Discussionmentioning
confidence: 98%
“…Physical inactivity is assessed through the estimation of physical activity. According to the WHO, physical activity is defined as any bodily movement produced by skeletal muscles, responsible for an increase in energy expenditure above the resting level [16]. It reduces weight, body mass index, cardiovascular disease and glycated haemoglobin levels, and improves glucose tolerance, insulin sensitivity and the cardio-respiratory system [17].…”
Section: Introductionmentioning
confidence: 99%